Gorenko V. The character of Mykola Lukash – the outstanding Ukrainian translator - Gorenko V. (Philological Treatises, 2020)
The article depicts the character of outstanding Ukrainian translator Mykola Lukash. He is exposed as a linguist with deep knowledge of Ukrainian language and a brilliant interpreter. The article is based on the observation of M. Lukash's work